Programa Pacto pela Aprendizagem (SOMA-PB): repercussões na gestão democrática estadual (2017-2019) - Fritschi, Christomyslley Romeiro da Silva (2022)
The overall objective of this investigation was to analyze the repercussions on educational democratic management in Paraíba, resulting from the implementation of the Pact for Learning in Paraíba (SOMA-PB) in the state public education system (2017-2019). The theoretical and methodological framework was developed based on contributions from dialectical materialism, encompassing the categories of mediation, contradiction, and totality. As methodological procedures and research techniques, semi-structured interviews were conducted with two participants involved in the implementation process of SOMA in Paraíba, along with an analysis of the normative documents that established the educational program. The interpretation and analysis of the information were grounded in critical discourse analysis. It was observed that the Pact for Learning in Paraíba (SOMA-PB), due to the implementation of recent national and local educational policies characterized by managerialism, seeks to operationalize strategies of results-based management and accountability of individuals, aiming to guide the functioning of the public educational network and, consequently, public schools, in line with practices in private companies. The educational policy derives from actions implemented during the Ricardo Coutinho administrations (2011-2014 / 2015-2018), based on the logic of modernizing management and managerial rationality, which advocates for efficiency in service provision. Within the organization of the state public education network in Paraíba, the Pact for Learning in Paraíba (SOMA-PB) consolidated neoliberal strategies, particularly in the activities of school teams responsible for achieving the goals agreed upon with the state education department, and introduced result control and monitoring as a means to align pedagogical and evaluative actions with what is defined by the program. We conclude that the conceptions of managerial management, materialized in the process of implementing the Pact for Learning in Paraíba (SOMA-PB), deepen the logic of performance evaluation, competition, and meritocracy in the education system by advocating, among other things, for the improvement of educational indices measured by external assessments. It reduces the subjective dimension of the teaching and learning process to the training of students through minimal content, guided by pragmatism, functionalism, and the pedagogy of competencies. Finally, within the scope of school administration, the Pact for Learning in Paraíba (SOMA-PB) redefined democratic principles. of participation, decentralization, and autonomy by instrumentalizing legitimized participation and the transfer of responsibilities, which empty the political meaning of democratic school management.